2016
DOI: 10.1093/dnares/dsw002
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome of healthy Japanese and its microbial and functional uniqueness

Abstract: The human gut microbiome has profound influences on the host's health largely through its interference with various intestinal functions. As recent studies have suggested diversity in the human gut microbiome among human populations, it will be interesting to analyse how gut microbiome is correlated with geographical, cultural, and traditional differences. The Japanese people are known to have several characteristic features such as eating a variety of traditional foods and exhibiting a low BMI and long life s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
340
10
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(397 citation statements)
references
References 47 publications
21
340
10
2
Order By: Relevance
“…Conversely, our results showed no relationship between the major energy source and bacterial abundance for any bacterial group. Determination of gut microbiota based on the 16S rRNA gene analysis method showed a greater abundance of Bifidobacterium in Japanese subjects than in subjects from other countries, especially those from the USA, China, and Korea, who showed a relatively low abundance (,2%) of Bifidobacterium (42,47). Likewise, our data showed a high abundance of Bifidobacterium in all of our Japanese subjects (average approximately 12%).…”
Section: Discussionsupporting
confidence: 61%
“…Conversely, our results showed no relationship between the major energy source and bacterial abundance for any bacterial group. Determination of gut microbiota based on the 16S rRNA gene analysis method showed a greater abundance of Bifidobacterium in Japanese subjects than in subjects from other countries, especially those from the USA, China, and Korea, who showed a relatively low abundance (,2%) of Bifidobacterium (42,47). Likewise, our data showed a high abundance of Bifidobacterium in all of our Japanese subjects (average approximately 12%).…”
Section: Discussionsupporting
confidence: 61%
“…Bacterial DNA was prepared as described previously [17]. In brief, bacterial DNA was extracted by enzymatic lysis using lysozyme (Sigma-Aldrich Co. LCC, Tokyo, Japan) and achromopeptidase (Wako).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, recent reports showed that the intestinal microbiome in the Japanese population is considerably different from those of other populations [17]. We already safely conducted FMT for Japanese patients with ulcerative colitis [18].…”
Section: Introductionmentioning
confidence: 99%
“…he genus Bifidobacterium represents one of the major components of the intestinal microbiota of breastfed infants (1)(2)(3)(4)(5) while also typically constituting between 2% and 10% of the adult intestinal microbiota (6)(7)(8)(9)(10)(11). Bifidobacteria are saccharolytic microorganisms whose ability to colonize and survive in the large intestine is presumed to depend on the ability to metabolize complex carbohydrates present in this environment (12,13).…”
mentioning
confidence: 99%